2021
DOI: 10.3233/bmr-191549
|View full text |Cite
|
Sign up to set email alerts
|

Immediate changes in trunk muscle activation patterns during a lifting task following an abdominal drawing-in exercise in subjects with recurrent low back pain

Abstract: BACKGROUND: The abdominal drawing-in exercise could help improve delayed transversus abdominis (TrA) activation during limb movement in subjects with recurrent low back pain (rLBP). However, little is known about whether the same effect is observed during lifting tasks in subjects with rLBP. OBJECTIVE: This study aimed to clarify whether a single session of abdominal drawing-in exercise could correct the altered trunk muscle activation patterns during a lifting task in subjects with rLBP. METHODS: Fifteen subj… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 47 publications
0
5
0
Order By: Relevance
“…Tsao et al reported that motor control exercises changed the onset timing of activity in the transversus abdominis muscle and that the intervention effect persisted 6 months later [ 45 ]. Additionally, the motor control exercise intervention has also been shown to decrease the activity of the global trunk muscle group in trunk active movements, lifting, and trunk external perturbation tasks [ 46 , 47 , 48 ]. Recent randomized control trials have reported that motor control exercise reduces pain intensity and functional impairment in NSCLBP, in addition to changes in the morphology of the trunk local muscle groups [ 49 ].…”
Section: Discussionmentioning
confidence: 99%
“…Tsao et al reported that motor control exercises changed the onset timing of activity in the transversus abdominis muscle and that the intervention effect persisted 6 months later [ 45 ]. Additionally, the motor control exercise intervention has also been shown to decrease the activity of the global trunk muscle group in trunk active movements, lifting, and trunk external perturbation tasks [ 46 , 47 , 48 ]. Recent randomized control trials have reported that motor control exercise reduces pain intensity and functional impairment in NSCLBP, in addition to changes in the morphology of the trunk local muscle groups [ 49 ].…”
Section: Discussionmentioning
confidence: 99%
“…Suehiro et al investigated whether a single session of abdominal drawing-in exercises could rectify the deviant activation patterns of trunk muscles observed during lifting tasks in individuals with recurrent LBP. The findings implied that abdominal drawing-in exercises might be efficacious in enhancing the recruitment pattern of muscles in individuals afflicted with recurrent LBP [ 6 ]. Masaki et al examined the activities of back muscles and sagittal spinal alignment in young males affected by LBP with a history during the performance of quadrupedal unilateral limb extension exercises.…”
Section: Semg In Massage Therapy and Rehabilitation Trainingmentioning
confidence: 99%
“…The paraspinal muscles play a crucial role in maintaining spinal stability, posture, and movement, making them a topic of significant interest and investigation in various fields, including biomechanics, rehabilitation, and sports medicine [ 3 , 4 , 5 , 6 , 7 ]. It was observed that there were some differences in paraspinal muscles among the individuals with LBP, such as the change in cross-sectional surface area and fat infiltration [ 8 , 9 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Breathing exercises are also effective in the treatment of musculoskeletal complaints, such as low back pain ( Kang et al, 2016 ; Ahmadnezhad et al, 2020 ; Otadi et al, 2021 ). For instance, the activation patterns of trunk muscles change immediately during the lifting task after performing an abdominal drawing-in exercise in subjects with recurrent low back pain ( Suehiro et al, 2021 ). A session of respiratory muscle training can also reduce the activity of some ankle joint muscles while performing overhead squats in athletes with chronic low back pain ( Borujeni and Yalfani, 2020 ).…”
Section: Introductionmentioning
confidence: 99%